Healthy Eating: Super Sandwiches - Jennifer Hillan; Emily Minton (EDIS, 2011)
Sandwiches make quick, easy, and nutritious meals. And here are some tips to create new sandwich favorites! This revised 1-page fact sheet was written by Jennifer Hillan and Emily Minton and published by the UF Department of Family, Youth and Community Sciences, July 2011.